Use of Waste & Recycled Material in Construction & Its Applications - Kumar, Tarun (Gyan Management Journal, 2020)
The primary objective of this research review is to find the possible utilization of different reused and  waste material and for final supply of those materials for Construction. As we are producing waste in  tones day by days so we need to utilize that waste in some different and efficient manner so that we can  reduce  that  threat  to  environment.We  are  increasing  loads  on  nation's  landfills  as  well.  For  economicviability andto find best solution for environment we can utilize the waste products and can  reuse them after suitable modification in their properties we can use them as some foreign to enhance  the mechanical, chemical and other properties of the building in addition to construction material. By  using these materials in construction we can reduce load on Nations landfills as well.Reuse of waste  materials helps to preserve natural resources, save energy, helps in to decrease solid waste, reduction in  pollution levels and other factors which effects our environment directly. Construction companies can  being aware and they can take the advantage by using these waste and recycled material. This review  paper discusses the implications  caused due to various waste products and features their  reusing  possibilities and  conceivable use for producing good  construction material. This paper deals with  proper use of waste and recycled material in construction and application in this field.
Keywords: Recycled material; Solid Waste; Environment; Construction Material